Investigating exclusive ρ0 photoproduction within the Regge phenomenology approach - László Jenkovszky; Érison S. Rocha; Magno V.T. Machado (Physics Letters B, 2022)
The elastic differential and integrated total cross section for the exclusive ρ0 photoproduction in electron-proton (ep) collisions are evaluated taking into account nonperturbative Pomeron exchange approach. By using three different models based on Regge phenomenology the results are compared to recent measurements by H1 Collaboration in ep collisions and by the CMS collaboration from ultraperipheral proton-lead collisions. The analysis is expanded by calculating the coherent nuclear cross section, σ(γA→ρ0A), which is applied to ρ0 production in ultraperipheral lead-lead and xenon-xenon collisions. The predictions are compared to the measurements performed by ALICE Collaboration. Aspects of the theoretical uncertainties and limitations of the formalism are scrutinized.